Masculinity Crisis: Phenomenon that Contributing to Violence Against Women as Ipact of Covid-19 Pandemic - Dwi Astuti; As Martadani Noor; Mukhijab Mukhijab; Paharizal Paharizal; Fahmi Rafika Perdama (Journal Of Social Science (JoSS), 2026)
This study aimed to explore the occurrence of a masculinity crisis in society during the COVID-19 pandemic and how this crisis influenced the tendency toward violent behavior against women in the household sphere. This research used a qualitative approach, specifically a case study design. The findings led to several conclusions. First, all informants still agreed that providing income is primarily a male responsibility. Second, differing constructions of masculinity were observed within families: in households where men had not worked from the beginning, there was greater acceptance of conditions in which women were more economically empowered. In contrast, informants who experienced job loss during the COVID-19 pandemic reported a stronger sense of crisis due to shifts in traditional gender roles. Third, overall perceptions of masculine dominance were no longer uniform, as informants expressed varied views. Fourth, when wives were more economically dominant, most men did not object as long as they remained employed.